(untitled) (Indian Journal of Chemistry (IJC), 2025)
An efficient approach has been described for the synthesis of substituted diaryl aromatic flava none-isoxazole (7a-m) hybrids through simple and practical methodology. The synthetic strategy involves formation of substituted diaryl flavanone aldoxime intermediates (5a-k) from substituted flavanone -3- aldehydes (4a-k) followed by [3+2] cycloaddition of in situ generated nitrile oxides with aryl acetylenes using sodium hypochlorite oxidant in THF in absence of light, furnished the functionalized isoxazoles with excellent yields (85-90%).